Answer:
x = 2
Explanation:
Solve for x:
4 x - 5 x - 3 + 1 = -4
Hint: | Group like terms in 4 x - 5 x - 3 + 1.
Grouping like terms, 4 x - 5 x - 3 + 1 = (4 x - 5 x) + (1 - 3):
(4 x - 5 x) + (1 - 3) = -4
Hint: | Combine like terms in 4 x - 5 x.
4 x - 5 x = -x:
-x + (1 - 3) = -4
Hint: | Evaluate 1 - 3.
1 - 3 = -2:
-2 - x = -4
Hint: | Isolate terms with x to the left hand side.
Add 2 to both sides:
(2 - 2) - x = 2 - 4
Hint: | Look for the difference of two identical terms.
2 - 2 = 0:
-x = 2 - 4
Hint: | Evaluate 2 - 4.
2 - 4 = -2:
-x = -2
Hint: | Multiply both sides by a constant to simplify the equation.
Multiply both sides of -x = -2 by -1:
(-x)/(-1) = 2
Hint: | Any nonzero number divided by itself is one.
(-1)/(-1) = 1:
Answer: x = 2